2022
DOI: 10.1177/11206721221123878
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptor agonist ramelteon alleviates experimental acute ocular inflammation via HIF-1Α/VEGF/E-NOS signaling

Abstract: Purpose Ramelteon (RML) is a potent, selective agonist of the high-affinity melatonin receptor 1 and 2 receptors. In addition, RML is known to have antioxidant and anti-inflammatory effects. In this study, we aimed to investigate the effects of RML on HIF-1α, VEGF and e-NOS signaling pathway in a rat model of endotoxin-induced uveitis (EIU). Methods Twenty-eight Wistar albino rats were divided into 4 groups as controls, lypopolysaccharide (LPS) group (5 mg/kg i.p.), LPS  +  RML group (5 mg/kg i.p and 8 mg/kg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We recently showed that the key angiogenesis regulatory gr dothelial growth factor A (VEGF-A), is a critical driver of huma in vivo and ex vivo [3]. In line with the "angiogenesis hypothes poses that a reduction in the production of angiogenic factors and capillary density promote tissue aging [90], we were interested i atonin exerted any impact on epidermal VEGF-A protein ex mainly been discussed in the literature as a candidate anti-angi counteract pro-angiogenic VEGF-A effects [91][92][93]. However, it reported to ameliorate aging-associated impaired angiogenesis [9 and/or VEGF receptor expression under some conditions [95,9 showed that melatonin treatment significantly increased the epid level of VEGF-A (Figure 3a,b).…”
Section: Melatonin Also Promotes Intraepidermal Production Of Vegf-a ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that the key angiogenesis regulatory gr dothelial growth factor A (VEGF-A), is a critical driver of huma in vivo and ex vivo [3]. In line with the "angiogenesis hypothes poses that a reduction in the production of angiogenic factors and capillary density promote tissue aging [90], we were interested i atonin exerted any impact on epidermal VEGF-A protein ex mainly been discussed in the literature as a candidate anti-angi counteract pro-angiogenic VEGF-A effects [91][92][93]. However, it reported to ameliorate aging-associated impaired angiogenesis [9 and/or VEGF receptor expression under some conditions [95,9 showed that melatonin treatment significantly increased the epid level of VEGF-A (Figure 3a,b).…”
Section: Melatonin Also Promotes Intraepidermal Production Of Vegf-a ...mentioning
confidence: 99%
“…In line with the "angiogenesis hypothesis of aging", which proposes that a reduction in the production of angiogenic factors and subsequently decreased capillary density promote tissue aging [90], we were interested in checking whether melatonin exerted any impact on epidermal VEGF-A protein expression. Melatonin has mainly been discussed in the literature as a candidate anti-angiogenesis factor that may counteract pro-angiogenic VEGF-A effects [91][92][93]. However, it has conversely also been reported to ameliorate aging-associated impaired angiogenesis [94] and to promote VEGF and/or VEGF receptor expression under some conditions [95,96].…”
Section: Melatonin Also Promotes Intraepidermal Production Of Vegf-a ...mentioning
confidence: 99%
“…For example, ramelteon protects the brain via relieving inflammation and oxidative stress though the Nrf2 signaling pathway ( 10 ). Ramelteon attenuates LPS-induced experimental acute ocular inflammation though hypoxia-inducible factor-1α/vascular endothelial growth factor/endothelial nitric oxide synthase signaling ( 11 ). Imai et al elucidated that ramelteon may alleviate the risk of vancomycin-induced nephrotoxicity ( 12 ).…”
Section: Introductionmentioning
confidence: 99%